FRI0425 Similar levels of disease activity in patients with oligoarticular vs. polyarticular peripheral spondyloarthritis. (23rd January 2014) - Van den Bosch, F.; Mease, P.; van der Heijde, D.; Rudwaleit, M.; Pangan, A. L.
Abstract : Background: The ASAS criteria for peripheral spondyloarthritis (SpA) allow for classification of patients with SpA who present with peripheral arthritis, enthesitis and/or dactylitis. 1 ABILITY-2, a placebo-controlled trial of adalimumab (ADA) for the treatment of peripheral SpA in patients not previously diagnosed with psoriasis or psoriatic arthritis (PsA), is the first pivotal study to use the ASAS criteria to classify patients for study entry. Objectives: This analysis characterizes ABILITY-2 patients based on gender and the pattern of joint involvement – oligoarticular vs. polyarticular. Methods: ABILITY-2 is an ongoing, randomized, controlled, multicenter, phase 3 study. Eligible patients were age ≥18 yrs, fulfilled ASAS peripheral SpA criteria, did not have a diagnosis of psoriasis, PsA, or ankylosing spondylitis, and had inadequate response or intolerance to NSAIDs. Required baseline disease activity at study entry included patient global assessment of disease activity (PGA) and of pain (PGA-pain) ≥40 mm (0–100 mm VAS), ≥2 SJC and TJC, ≥2 digits with dactylitis or enthesitis accompanied by at least 1 joint with active arthritis, or ≥2 sites with enthesitis judged to be severe by the investigator. Subgroup analyses of baseline demographics and disease activity were conducted by gender and by pattern of joint involvement, oligoarticular (2–4 joints either tender and/or swollen) vs. polyarticular (>4 joints that are either tender and/or swollen). Results: Of the 165 patients randomized, 90 (54.5%) were female; 125 (75.8%) had polyarticular disease. Females were slightly older (42.3 vs. 38.5 years), and had a lower proportion with HLA-B27 positivity (58.4 vs. 65.3%), but overall, displayed similar disease activity parameters as males. Predominantly lower limb involvement was observed at baseline in 57% of males, 50% of females, 59% of patients with oligoarticular disease, and 51% of patients with polyarticular disease. More patients with polyarthritis were HLA-B27+ (62.1%) compared to those with oligoarthritis (52.9%). Although fewer polyarticular patients had an abnormal hs-CRP at baseline (42.4% poly vs. 52.9% oligoarticular), the mean hs-CRP was higher in those with polyarticular disease. The proportion of patients with accompanying enthesitis or dactylitis at baseline was also greater in those with polyarticular disease (poly- vs. oligoarticular): Leeds enthesitis index >0 (68.0% vs. 44.1%), SPARCC >0 (81.6% vs. 64.7%), MASES >0 (80.0% vs. 52.9%), and dactylitis count >0 (27.4 vs. 8.8%). Patient and physician global assessments, BASDAI, HAQ-S, and the physical component score of the SF-36v2 were similar between these 2 subgroups. Conclusions: In non-PsA peripheral SpA patients with inadequate response or intolerance to NSAIDs, similar levels of disease activity, as measured by patient and physician global assessments, were observed regardless of extent of joint involvement. Likewise, functional impairment was also comparable between patients with oligo- and polyarticular joint disease. References: Rudwaleit M et al. Ann Rheum Dis 2011;70:25–31. Acknowledgements: AbbVie contributed to study design, research, analysis, data collection, interpretation of data, and writing, reviewing and approving the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, and Douglas E. Dylla, PhD, of AbbVie. Disclosure of Interest: F. Van den Bosch Consultant for: AbbVie, Merck, Pfizer, UCB, Speakers bureau: AbbVie, Merck, Pfizer, UCB, P. Mease Grant/research support from: AbbVie, Amgen, BiogenIdec, BMS, Genentech, GSK, Janssen Lilly, Merck, Merck-Serono, Novartis, Novo-Nordisk, Pfizer, Roche, UCB, and Vertex, Consultant for: AbbVie, Amgen, BiogenIdec, BMS, Genentech, GSK, Janssen Lilly, Merck, Merck-Serono, Novartis, Novo-Nordisk, Pfizer, Roche, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, BiogenIdec, BMS, Genentech, GSK, Janssen Lilly, Merck, Merck-Serono, Novartis, Novo-Nordisk, Pfizer, Roche, UCB, and Vertex, D. van der Heijde Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli-Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli-Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, Employee of: Imaging Rheumatology bv, M. Rudwaleit Consultant for: AbbVie, BMS, Centocor, Chugai, MSD, Novartis, Pfizer, Roche, and UCB, A. Pangan Shareholder of: AbbVie, Employee of: AbbVie